Antidiabetic Activity of an Ayurvedic Formulation Chaturmukha Rasa: A Mechanism Based Study - Akansha Sharma; Raj K Tiwari; Vikas Sharma; Ravindra K Pandey; Shiv Shnakar Shukla (Korean Pharmacopuncture Institute, 2019)
Objectives: The objective of this study was to evaluate antidiabetic activity of Chaturmukha rasa based on streptozotocin induced diabetes model, alpha amylase inhibitory activity, alpha Glucosidase inhibitory activity and inhibition of sucrase. Methods: Chaturmukha rasa was prepared as per Ayurvedic formulary. Antidiabetic activity was measured in experimentally streptozotocin induced rats. The dose was taken as 45 mg/kg, i.p. The antidiabetic activity of Chaturmukha rasa was compared Triphala Kwatha, a marketed formulation. Further In vitro ά- Amylase Inhibitory Assay, In vitro salivary amylase Inhibitory Assay, In vitro α-Glucosidase Inhibitory Assay and In vitro Sucrase Inhibitory Assay was performed with respect to Chaturmukha rasa . The IC50 value was calculated for all the above activity. Results: Streptozotocin with Acarbose showed significant decrease in blood glucose level whereas streptozotocin with Triphala kwatha showed more decrease in blood glucose level than Streptozotocin with Acarbose. The combination of Streptozotocin + Triphala kwatha + Chaturmukha rasa showed a significant decrease in blood glucose level on 21st day. In vitro ά- Amylase Inhibitory Assay the Chaturmukha rasa showed IC50 value 495.94 μl when compared with Acarbose 427.33 μl, respectively. In the α-Glucosidase Inhibitory Assay Chaturmukha rasa showed IC50 value 70.93 μl when compared with Acarbose 102.28 μl, respectively. In vitro Sucrase Inhibitory Assay Chaturmukha rasa showed IC50 value 415.4 μl when compared with Acarbose 371.43 μl, respectively. Conclusion: This study supports that Chaturmukha rasa may inhibit diabetes by inhibition of salivary amylase or alpha Glucosidase or sucrase. This may be the mechanism by which Chaturmukha rasa inhibits diabetes. Further this study supports the usage of Chatur mukha rasa for the management of diabetes.